Digital transformation of companies in the Western Balkans - Kelečević, Teodora (International journal of management, knowledge and learning, 2025)
Purpose: This paper assesses the state of digital transformation in the Western Balkans and identifies key opportunities and barriers to competitiveness, sustainable development, and integration into the European Single Digital Market. Methodology: A comparative, indicator-based analysis is applied, combining statistical data, policy review, and a focus on small and medium-sized enterprises (SMEs) and national strategies. Findings: Results reveal significant disparities: Croatia and Slovenia are near EU benchmarks, while Albania, Bosnia and Herzegovina, and North Macedonia lag due to weak digital skills and infrastructure. Advancing human capital, SME digital adoption, and supportive policy frameworks is essential for competitiveness and EU integration. Contribution: The study provides one of the few comparative analyses of digital transformation in the Western Balkans, offering new insights on SMEs, structural barriers, and policy measures.
Keywords: companies; digital transformation; digital world; digitalizacija; digitalization; digitalna transformacija; digitalni svet; management; podjetja; Western Balkans; Zahodni Balkan